CHEMSEX RELATED SEXUAL BEHAVIOURS AND SEXUALLY TRANSMITTED INFECTIONS AMONG MEN WHO HAVE SEX WITH MEN IN BELGRADE - Bjekić, Milan; Salemović, Dubravka; Vlajinac, Hristina; Marinković, Jelena (HEALTH CARE, 2024)
Background/Aim: Chemsex is a common practice among men who have sex with men (MSM). The aim of this study was to assess the prevalence of chemsex in the MSM population in Belgrade and its association with their behaviour and sexually transmitted infections. Metods: A cross-sectional study was conducted at two institutes in Belgrade over a six-month period and it covered 469 MSM. Data on demographic characteristics, reasons of attendance, sexual history, sexual behaviour and sexualized drugs use in the previous six months were collected from all participants by the use of a questionnaire. Results: Chemsex was practiced by 123 (26.2%) participants and GHB/GBL was most commonly used (84.6%). According to the results of multivariate logistic regression analysis those practicing chemsex differed from other participants significantly, independently of other factors, in the following characteristics: they were more frequently employed (Odds Ratio – OR=2.50, 95% confidence interval – 95%CI=1.19-5.26, p=0.015), had a greater number of sex partners in the last six months (OR=1.39, 95%CI =1.14-1.72, p=0.002), had condomless anal sex (OR=3.23, 95%CI=1.64-6.25, p=0.001) and group sex more frequently in the last six months (OR=4.35, 95%CI= 2.38-7.69, p<0.001), used a greater quantity of alcohol (OR=2.50, 95%CI 1.54-4.00, p<0.001), and had bacterial STIs more frequently in the last year (OR=2.70, 95%CI=1.61-4.54, p<0.001). The frequency of recreational drugs use was lower in those engaged in chemsex (OR=0.59, 95%CI=0.41-0.88, p=0.009). Conclusion: MSM engaged in chemsex practiced high risk sexual behaviour and suffered from bacterial sexually transmitted infections more frequently. The growing phenomenon of chemsex among MSM requires raising awareness about issues regarding chemsex both among the members of this vulnerable population and healthcare workers